Angiotensin II protects cortical neurons against oxygen-glucose deprivation-induced injury in vitro - TANG, MINGTAN (D.A. Spandidos, 2014)
Ischemic cerebrovascular disease is a common type of cerebrovascular disease and the leading cause of disability and mortality worldwide. Therefore, it is crucial to elucidate its pathogenesis and develop novel therapeutic strategies. This study was performed to investigate whether angiotensin (Ang) II exerts a protective effect against cerebral ischemia/reperfusion (I/R) injury in vitro. The primary cultured neurons were prepared and an I/R model was established by incubation of cortical neurons with Na(2)S(2)O(4), followed by culture in fresh medium. The protective effect of Ang II and its underlying mechanisms were investigated by morphology observation, MTT assay, flow cytometry analysis and reverse transcription-polymerase chain reaction (RT-PCR). The data demonstrated that Ang II significantly ameliorated the neuronal injury caused by oxygen-glucose deprivation. Furthermore, Ang II increased cell viability through inhibiting cell apoptosis. The RT-PCR results revealed that Ang II was able to reverse the increased bax mRNA and the decreased bcl2 mRNA expression. Of note, the protective activity of Ang II may be attenuated by co-treatment with Ang II type 2 (AT2) receptor blockade (PD123319), but not Ang II type 1 (AT1) receptor blockade (valsartan). These findings suggested that Ang II exerted a protective effect against neuronal injury induced by oxygen-glucose deprivation through decreasing cell apoptosis. Therefore, Ang II may be used as a potential therapeutic target in the future.